Manfaat Ekstrak Daun Sirih (Piper betle Linn) sebagai Han Sanitizer untuk Menurunkan Angka Kuman - Dewita Nungki Hapsari; Lilik Hendrarini; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2015)
Daun sirih (Piper betle Linn) plant contains antiseptic substance that can kill bacteria and fungiand have capacity as antioxidant. Hand sanitizer is hand cleaner without the use of water thatcan block the growth of and even kill bacteria. The purpose of this research was to know the influence of hand sanitizer with Piper betle Linn leaves extract on the reduction of hand microbenumber by conducting a pre-test post-test gorup designed experiment. As the study subject was36 sixth grade students of Pedes 1 Elementary School of Sedayu, Bantul, who were divided intothree treatment groups, i.e. hand sanitizer with extract Sirih leaves of 10 %, 20 %, and 30 % concentrations. The microbe numbers were examined at The Laboratory of Health of YogyakartaProvince, and the results showed that 10 % concentration was able to reduce 507,75 colony/cm2or 77,92 %; meanwhile the 20 % and 30 % concentrations were of 3967,75 colony/cm2 or 86,13%; and 776,08 colony/cm2 or 93,94 %, respectively. The one way anava test at 95 % confidencelevel proved that those differences are significant (p-value<0,001) and the subsequent LSD testconcluded that 20 % is the most effective concentration.